PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR SISWA ( Studi Pada Muatan Pelajaran IPA Kelas V SD Negeri 1 Pagar Alam ) - Yepi Riska; Alexon Alexon (UNIB Press, 2021)
This study aims to describe the application of the Number Heads Together cooperative learning model in increasing self-confidence and learning achievement of grade V students of SD Negeri 1 Pagar Alam. The research design used was classroom action research and quasi-experimental. The subjects of classroom action research (PTK) were students of class V.A even semester of the 2020/2021 school year SD Negeri 1 Pagaralam. For the quasi-experimental sample, the classes V.B and V.C. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results showed that: First, the application of the Number Heads Together cooperative learning model can increase students' self-confidence. Second, the application of the Number Heads Together cooperative learning model can improve student achievement. Third, the application of the Number Heads Together cooperative learning model is more effective in improving student learning outcomes compared to conventional methods. The conclusion of the research is that the Number Heads Together cooperative learning model can increase self-confidence and student achievement and is more effective in increasing student achievement compared to conventional learning.